Presence of luminal neutrophil extracellular traps in atherosclerosis - Megens, Remco T. A.; Vijayan, Santosh; Lievens, Dirk; Döring, Yvonne; van Zandvoort, Marc A. M. J.; Grommes, Jochen; Weber, Christian; Soehnlein, Oliver (Thrombosis and Haemostasis, 2012)
Note: The editorial process for this article was fully handled by Prof. G. Y. H. Lip, Editor-in-Chief.